THE ROLE OF HUMAN RESOURCES IN DETERMINING EXCHANGE RATE FOR FARMERS OF FOOD CROPS IN EAST TANJUNG JABUNG REGENCY JAMBI PROVINCE - Saiyid Syekh (Dinasti Publisher, 2020)
The research to porpose : (1) to know the farmers exchange rate in East Tanjung Jabung Regency; (2). To identify and analyze the determining factors of the exchange rate of farmers in East Tanjung Jabung Regency. (3). To analyse the role of HR (human resources) the exchange rate of farmers in East Tanjung Timur regency. This research used survey methode with porposive sampling in sub district: population of sub district in East TanjungJabung are 11 sub district, with sample amounth 5 sub district. The resulth of this research farmer's of food crops exchange rate in East Tanjung Jabung is at a point close to one hundred. This means that although farmers are still categorized as profit in the cultivation of agricultural crops and horticultural but the condition is very risky, because in addition to only comparable, also if subsidies and various assistance is not there, then farmers will tend to lose, except the district Geragai which farmers exchange rate its above 150%. Human Resourches role is very dominant because in addition can manage the efforts ranging from preharbest handling to post Harberst handling.